Long-term underperformance of public versus rights offering firms - Hyun Ju Kim; Kyojik Roy Song (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2022)
The authors compare the post-issue stock and operating performance of rights issue versus public offer firms using Korean data. The authors find that the stock returns of rights issue firms are less negative than those of public offering firms during the three years subsequent to the seasoned equity offering. The authors further find that the profitability of rights offering firms is superior to those of public offering firms and that the ratio of sales to assets for rights issue firms is much higher over the post-issue period. The results substantiate Heinkel and Schwartz's (1986) and Eckbo and Masulis' (1992) theoretical models that posit firms with better quality tend to select the rights issue rather than public offer method when issuing seasoned equity.
Keywords: G30; 330; Seasoned equity offering; Rights issue; Public offer; Long-term performance